40th AIAA Aerospace Sciences Meeting &Amp; Exhibit 2002
DOI: 10.2514/6.2002-124
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of synthetic jets to the design of the jet cavity

Abstract: The sensitivity of synthetic jets to the design of the jet cavity is examined using numerical simulations. In this study, the primary focus is on examining the effect of changes in the cavity aspect ratio and the placement of piezoelectric diaphragm on the flow produced by the jet. Cases with and without an external cross-flow are investigated. This study compares the vortex dynamics, velocity profiles and other dynamical characteristics of the jet for the various cases and this allows us to extract some insig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(30 citation statements)
references
References 11 publications
2
28
0
Order By: Relevance
“…A cavity with a very large separation between the opening and the back of the cavity may never experience impingement, whereas SJAs with very shallow cavities have been observed to generate arrays of counter-rotating vortices within Pressure and work of deformable jet producing cavity bodies the cavity, especially when a crossflow is present (Utturkar et al 2002). Unlike the previous three subsections, where the other sources of vorticity are modelled for any general cavity body, this section will focus on modelling circulation from vortex ring impingement for the particular case where the back cavity surface has a curvature which is small compared to the opening diameter, and where separation, h, is small enough to facilitate impingement, similar to the experimental actuator.…”
Section: Vortex Ring Impingement and Boundary Layer Formationmentioning
confidence: 98%
“…A cavity with a very large separation between the opening and the back of the cavity may never experience impingement, whereas SJAs with very shallow cavities have been observed to generate arrays of counter-rotating vortices within Pressure and work of deformable jet producing cavity bodies the cavity, especially when a crossflow is present (Utturkar et al 2002). Unlike the previous three subsections, where the other sources of vorticity are modelled for any general cavity body, this section will focus on modelling circulation from vortex ring impingement for the particular case where the back cavity surface has a curvature which is small compared to the opening diameter, and where separation, h, is small enough to facilitate impingement, similar to the experimental actuator.…”
Section: Vortex Ring Impingement and Boundary Layer Formationmentioning
confidence: 98%
“…It has been previously shown that the behavior of the flowfield emanating from the slot is primarily sensitive to the cavity volume and not its shape. 23 The oscillatory diaphragm properties include the angular frequency of oscillation ω, its fundamental resonant frequency ω d , and the volume displaced by it ∀, whereas the relevant fluid properties are the isentropic speed of sound c 0 and the kinematic viscosity ν. These 11 parameters contain the two primary dimensions of length and time; thus, there are 9 dimensionless parameters.…”
Section: Vortex-based Jet Formation Criterionmentioning
confidence: 99%
“…One such method consists of applying, a typically macro scale concept, the synthetic jet. Synthetic jets (Glezer and Amitay, 2002;Mittal et al, 2001;Mittal and Rampunggoon, 2002;Utturkar et al, 2002) have proven to be a useful meso and micro fluid device with applications including thrust vectoring, mixing enhancement, control of boundary layer separation and turbulence control. Synthetic jets are formed from alternating suction and ejection of fluid across an orifice with zero net mass flux.…”
Section: Introductionmentioning
confidence: 99%